(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Strengthening can be done by means of different materials. Steel plate is one of the most frequent materials for strengthening of RC structures. It increases the shear and flexural capacity of RC beam due to its cheapness, availability, high fatigue and high ductility strength. FRP materials are showing good results using epoxy glue for strengthening RC structures. This paper shows the strengthening of R.C. beams using CFRP sheets, GFRP sheets and Mild steel plate in different types. FRP sheets are bonded at tension side (bottom) and up to neutral axis (U shape) of the beam. Mild steel plates are bonded on bottom of beam in two different types i.e. with epoxy glue and bolt. Among all the type, CFRP gives better results than others. Mild steel plate also gives good results, but due to bad material properties of mild steel plate, CFRP will be the best for strengthening using epoxy.